Indigenous knowledge of Malay culture and Islamic professional madrasa teachers: a phenomenological investigation - Tambak, Syahraini; Sukenti, Desi; Firdaus, Firdaus (Institute of Advanced Engineering and Science, 2024)
Same research has been done on professional madrasa teachers, but incorporating Islamic values and indigenous knowledge of Malay culture into them has been neglected. This study aims to determine Islamic professional madrasa teachers based on indigenous knowledge of Malay culture in the teaching for future profession. This study used a phenomenological research design involving 16 madrasa teachers as informants. Data was collected by conducting interviews with madrasa teachers and analyzed using a systematic design. This research shows that Islamic professional madrasa teachers are related to prophetic abilities based on Islamic values, moral, and related to human functions as khalifah, imarat al-ard, and ‘abdullah. Indigenous knowledge of Malay culture is an integral part of developing Islamic professional madrasa teachers, contribute to producing attitudes there are in accordance with Islam and having commendable qualities. Madrasa teachers have the ability the rules of Fiqh: al-‘adatu muhakkamat, istihsan, ‘urf, and maslahah al-mursalah to integrate Malay cultural values in learning materials. Self-control, ukhuwah, religious moderation, and an attitude of pluralism contained in Malay culture are the basis for the personality competence of Islamic professional madrasa teachers in learning. This research has implications for developing theories of professional Islamic madrasa teachers for the future profession.